2018
DOI: 10.1159/000490134
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Protects the Kidney by Regulating the Effect of TNF-α in L-NAME-Induced Hypertensive Rats

Abstract: Background/Aims: Hypertension is the leading cause of death worldwide. Chronic high blood pressure induces inflammation. Tumor necrosis factor (TNF)-α plays a major role in inflammation and also depresses the synthesis of erythropoietin, which exerts protective effects on tissue; however, the mechanism is still unclear. We investigated the protective effect of erythropoietin against tissue damage caused by hypertension in the kidney and whether this effect was suppressed by TNF-α. Methods: First, we detected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(33 reference statements)
0
1
0
1
Order By: Relevance
“…In vivo and in vitro studies on astrocytes have shown that TNF- α suppresses hypoxia-induced Epo expression also in a dose-dependent manner [ 11 ]. In our previous study, we have shown that elevated levels of TNF- α in hypertension decreased the amount of Epo in the circulation and that circulating Epo concentrations increased to normal values when TNF- α was blocked with anti-TNF- α antibodies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo and in vitro studies on astrocytes have shown that TNF- α suppresses hypoxia-induced Epo expression also in a dose-dependent manner [ 11 ]. In our previous study, we have shown that elevated levels of TNF- α in hypertension decreased the amount of Epo in the circulation and that circulating Epo concentrations increased to normal values when TNF- α was blocked with anti-TNF- α antibodies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Outra função da EPO é proteger contra injúria renal, reduzindo a apoptose e a inflamação e aumentando a proliferação tubular (179). A EPO renal é expressa principalmente pelos pericitos (células semelhantes a fibroblastos) e em um quadro de DRC, essas células se transdiferenciam em miofibroblastos cuja capacidade de produção de EPO é reduzida (180).Achados corroboram a ideia de que a interação entre EPO e NO representam um mecanismo relevante de atenuar os danos causados pela hipertensão (181)(182)(183) e que a exposição à hipóxia crônica pode ser uma estratégia terapêutica para elevar os níveis de EPO e outros mecanismos associados a redução da inflamação.…”
Section: Componentes Do Sinal 1 Da Imunidade Inataunclassified